Is Europe disintegrating? Macroeconomic divergence, structural polarization, trade and fragility - Claudius Gräbner; Philipp Heimberger; Jakob Kapeller; Bernhard Schütz (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2017)
This paper analyses economic developments in the Eurozone over the period 1999-2016 by developing a theoretical framework that traces divergent path developments across Eurozone countries to the times before the financial crisis. We argue that macroeconomic divergence between core and periphery countries is driven by 'structural polarization' in industrial structures: the emergence of export-driven growth in the core and debt-driven growth in the periphery is linked to the micro level of technological capabilities and firm performance. Pushing for convergence within Europe requires the simultaneous implementation of three intertwined policy programs: coordinated macroprudential financial regulation, active industrial policies aiming at a catching-up process in terms of innovative activity and technological capabilities for firms in the European periphery, and progressive re-distributional policies.
Keywords: B5; E6; F45; 330; Polarization; European Monetary Union; industrial policy; financial regulation; growth trajectories